2018
DOI: 10.5812/aapm.57583
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Disease Severity and Calcium Concentration in Critically Ill Patients Admitted to Intensive Care Unit

Abstract: BackgroundHypocalcemia is very common in critically ill patients admitted to ICU. However, its clinical importance and relation to patient’s outcome during early days of ICU admission is questionable. Based on the mentioned problem, it seems that calcium assessment is highly important in these patients. The present study aimed at evaluating the relationship between different calcium concentrations (total/ionized/corrected) and disease severity in critically ill patients.MethodsA total of 100 patients admitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Studies have shown that both total calcium and adjusted calcium ion concentrations in ICU experimental group patients can assess disease severity to a certain extent [21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that both total calcium and adjusted calcium ion concentrations in ICU experimental group patients can assess disease severity to a certain extent [21].…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that hypocalcemia in hospitalized patients with COVID-19 and its association with more severe COVID-19 may be a marker of severe illness. Indeed, it was shown that hypocalcemia was common in patients with critical disease admitted to the ICU and was associated with poor prognosis [13].…”
Section: Mechanisms Of Hypocalcemia In Covid-19mentioning
confidence: 99%
“…Traumatic brain injury (TBI) is one of the common causes of long-term disabilities and mortality. Each year, about 50,000 people in the United States alone and 10 million worldwide die due to TBI (1)(2)(3)(4)(5). Treatment-related costs in patients with TBI imposes a heavy economic burden on the individual and the society due to poor recovery process, long-term disability, and its higher incidence in young people.…”
Section: Introductionmentioning
confidence: 99%